Integrasi Triadik Tafsir al-Qur’an: Upaya Penyelesaian Problem Kontemporer Indonesia - Luthfi Maulana; Shinta Nurani (Living Islam: Journal of Islamic Discourses, 2018)
Islam is a religion raḥmatan lil ‘ālamīn and has major source of al-Qur’an shalih li kulli zaman wa makan that contains everything about human life, but the Koran can’t speak for themselves; it requires the efforts of dialogue between man and the Koran to dynamic the verses of the Koran in human life anywhere and anytime, including in Indonesia in the contemporary era. Indonesia is the largest and poverty issues. A variety of complex issues in Indo- nesia can be solved by using an alternative solution offers integration concept triadic that includes the integration between Islam, Indonesia, and science, by constructed the concept of triadic that Islam expected more grounded and dynamic in society to address the problems of contemporary Indonesian.Muslim population in the world. But although Indonesia is categorized as the largest Muslim country, as a heterogeneous country, Indonesia has a lot of issues of particular concern and should be resolved quickly and accurately, the problems faced by Indonesia most such as corruption.